Analisis Penentuan Letak Trafo Distribusi Pada Penyulang Walmas Menggunakan ETAP Power Station 12.6.0 - Arifyanto, Dedy (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2023)
Distribution transformers are devices designed to transmit electrical energy from the power source to consumers. The loading percentage on distribution transformers must not exceed the health index standard of 80% of their capacity, in accordance with the regulations of PT.PLN (Persero) as stated in directorate circular Number: 0017.E/DIR/2014. In addition to the loading percentage, the voltage variation in electrical distribution must comply with the specified limits of +5% and -10% from the nominal voltage as per SPLN No.1 of 1995. This research was conducted to analyze one of the distribution transformers that experienced overload, leading to a voltage drop in the electrical network system, necessitating appropriate measures to address the issue. The load forecasting for determining the capacity and lifespan of transformers is conducted using the Least Square method. Data from 2022 shows that the distribution transformer with the code